Rancang Bangun Mesin Penggilingan Padi Rumahan dengan Penggerak Dinamo Pompa Air - Muhammad Iqbal Harapan Muslim Siregar; Bukhari; Tomi Abdilah; Tomi Irawan; Ali Hasimi Pane; Tengku Jukdin Saktisahdan (G-Tech: Jurnal Teknologi Terapan, 2024)
Currently, the rice milling process in Rawang Panca Arga Sub-district still uses a diesel car engine as the driving force. This machine has several drawbacks and emits harmful pollutants that are detrimental to respiratory health. Therefore, a compact and highly portable equipment was developed to meet the rice needs of farmers easily, without causing pollution. This rice milling machine uses a water pump dynamo that uses 125 Watts of electric current with a rotation of 2800 rpm and has a power of 3.28154 KW. The motor transmits its rotation using two clutches that can rotate the shaft of the penyosoh axle which is supported by two pillow block bearings. This machine has a grinding chamber with a maximum capacity of 72 kg/houre which is suitable for home-scale use.